Current Control of BLDC Drives for EV Application - Noor Azam, Ahmad Faiz; Jidin , Auzani; Ngatiman, Nor Azazi; JOPRI, MOHD HATTA; Manap, Mustafa; Lukar Herlino, Adeline; Alias, Nor Faezah (2013)
This paper presents a current blocking strategy of brushless DC (BLDC) motor drive to prolong the capacity voltage of batteries per charge in electric vehicle applications. The BLDC motor employs a simple torque hysteresis control (THC) that can offer a robust control and quick torque dynamic performance. At first, a mathematical modeling of BLDC motor and principle of torque hysteresis control will be described, so that the benefit offered by the proposed current blocking strategy can be highlighted. It can be shown that the current control method naturally provides current limitation, in which the current error (or ripple) is restricted within the pre-defined band-gap furthermore provide current protection. The benefit of proposed current blocking strategy will be highlighted such that it can prevent the current drained from the batteries when the torque demand is released to set to 0 Nm. The control scheme is validated and verified by the simulation and experimental results.